IMPLEMENTASI KEBIJAKAN DAERAH KABUPATEN CIAMIS TERHADAP PERLINDUNGAN TANAH ULAYAT MASYARAKAT ADAT KAMPUNG KUTA - Adrian Ramadan; Aan Anwar Sihabudin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The recognition and protection of indigenous peoples' customary lands is a crucial issue in the context of regional autonomy in Indonesia. Ciamis Regency has enacted Regional Regulation No. 15 of 2016 as a legal umbrella for the indigenous community of Kampung Kuta, but its effective implementation still faces various challenges. This study aims to analyze the implementation of regional policies in protecting the customary lands of the indigenous people of Kampung Kuta and to identify obstacles and efforts to strengthen it. This study uses a qualitative approach with a case study design. Data were obtained through in-depth interviews with the traditional leader of Kampung Kuta (Aki Warja), field observations, and document studies in the form of regional regulations and official government sources. The results show that the Regional Regulation has provided sufficient legal legitimacy for the existence and customary rights of indigenous peoples. However, its implementation has not been optimal, especially in terms of policy dissemination, institutional coordination, and community participation. The novelty of this research lies in revealing the gap between normative legal recognition and policy implementation practices at the local level based on the direct experiences of indigenous peoples. This research contributes to enriching the study of regional policy implementation and provides recommendations for strengthening the sustainable protection of customary land.